LETTER OF GUARANTEE AS PART OF DOCUMENT: COMPARATIVE DESCRIPTION OF THE DOCUMENT ON RUSSIAN AND PORTUGUESE - Pudikova, G.N. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The article deals with morphological features of Russian and Portuguese texts of Document on the example of letters of guarantee. Choosing a theme is caused by the development of traditions of busi-ness turnover in Russia and the countries where Portuguese is the official language, expanding international cooperation, economic globalization, the construction of the Information Society, which require a compre-hensive study of theoretical, methodological and practical approaches in the field of lexical content of documents of business turnover. The relevance of the work is determined by the following reasons: globalization of international business ties, which leads to the formation of unified approaches and standardization of business correspond-ence; Actively developing information technologies, which leads to a reduction of barriers in the formation of business correspondence; Occurring in connection with the globalization of the economy and the infor-matization of society changes in the national vocabulary and business culture. The purpose of the work is to consider the morphological features of Russian and Portuguese documentary texts on the example of guarantee letters. The author has identified the following objectives: to determine the content of the letter of guaran-tee and especially its preparation; an analysis of morphological features of letters of guarantee in the Russian and Portuguese. The subject of research is the lexical peculiarities of drawing up documents in Russian and Portuguese. The sources used in the work: normative legal acts of the Russian Federation, doctoral research, literary sources on the studied subject, published in the periodical press and Internet materials. The object of research is the rules and traditions of business turnover.